Formal University Education and Job Competency of New Engineers in Automotive Industry in Malaysia - Chan, Yuen Fook; Selvam, Balaram (2016)
The main purpose of this research is to verify the relevancy of knowledge and skills acquired by engineering graduates from university to automotive industry in Malaysia. Hence, this paper aims to identify to what extent the knowledge and skills acquired by the new engineers in the university have equipped them with job competency in the automotive industry. This study adopts a qualitative case study method to analyze and compare data collected from a private engineering college, a public university and an automotive manufacturing industry. The identified target groups are one human resource manager, six new engineering graduates, and 4 university lecturers. The findings of this study suggested that the stakeholders, university, students as well as industries are aware that it is not easy for new engineers to fit into industries right after graduation. The study emphasizes the important role of the stakeholders namely; university, new engineer and industry, to enhance the acquisition of knowledge and skills for better job competency of new engineers at the beginning of their career at industry.The results revealed certain attributes showing strong linkage between university education and job performance. In particular, students’ attitude,interpersonal skills, lack of manufacturing knowledge, lecturers’ industrial exposure, collaboration between university and industry, poor execution of internship, poor training needs analysis and incompetent coach at industry were among the attributes that have high influence on the ability of new engineers coping with the job challenges. The study has contributed to a better understanding of job competency and the challenges faced by new engineers at the chosen automotive industry.